2015
DOI: 10.3892/ijmm.2015.2114
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-β1 regulates chondrocyte proliferation and apoptosis through the upregulation of GIT1 expression

Abstract: Chondrocytes play a critical role in the repair process of osteoarthritis, which is also known as degenerative arthritis. Integrins, as the key family of cell surface receptors, are responsible for the regulation of chondrocyte proliferation, differentiation, survival and apoptosis through the recruitment and activation of downstream adaptor proteins. Moreover, G-protein-coupled receptor kinase interacting protein-1 (GIT1) exerts its effects on cell proliferation and migration through interaction with various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 31 publications
(64 reference statements)
1
31
0
1
Order By: Relevance
“…A recent study [11] demonstrated that miR-206 overexpression significantly inhibited the proliferation, promoted chondrocyte apoptosis, dramatically decreased Col2a1 and aggrecan, and increased Runx2 and MMP-13 [11], indicating the involvement of miR-206 in cartilage degradation in OA. Furthermore, GIT1 has been shown to promote chondrocytes proliferation and inhibit chondrocytes apoptosis [12][13][14]. In the current study, we verified not only the direct binding between KLF3-AS1 and miR-206, but also 3ʹUTR of GIT1 and miR-206.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A recent study [11] demonstrated that miR-206 overexpression significantly inhibited the proliferation, promoted chondrocyte apoptosis, dramatically decreased Col2a1 and aggrecan, and increased Runx2 and MMP-13 [11], indicating the involvement of miR-206 in cartilage degradation in OA. Furthermore, GIT1 has been shown to promote chondrocytes proliferation and inhibit chondrocytes apoptosis [12][13][14]. In the current study, we verified not only the direct binding between KLF3-AS1 and miR-206, but also 3ʹUTR of GIT1 and miR-206.…”
Section: Discussionsupporting
confidence: 71%
“…Extensive research has shown that G-proteincoupled receptor kinase interacting protein-1 (GIT1) promotes chondrocytes proliferation and inhibits chondrocytes apoptosis [12]. Zhao et al [13] stated that platelet-derived growth factor (PDGF) promotes chondrocyte proliferation but suppresses chondrocyte apoptosis via upregulating GIT1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies showed that lncRNA KLF3 Antisense RNA 1 (KLF3‐AS1) in MSC‐Exos promoted the G‐protein‐coupled receptor kinase interacting protein‐1 (GIT1) expression through a miRNA‐206 sponge effect and alleviated the IL‐1β‐induced chondrocyte apoptosis and inhibition of proliferation. In addition, GIT1 promoted the chondrocyte proliferation and inhibited the chondrocyte apoptosis by increasing the aggrecan and Type II collagen expression . These data suggest that MSC‐Exos can improve OA by transferring lncRNAs to chondrocytes to regulate gene expression related to chondrocyte proliferation and can be used as a potential therapy for OA.…”
Section: Introductionmentioning
confidence: 73%
“…Meantime, based on our present and previous results, periodic mechanical stress-activated GIT1 and Tyr 397 signals may act in parallel in this setting. Recently, GIT1 was viewed as an important integrin-associated kinase that receives and transmits various integrin-initiated intracellular biochemical signals [16,41,42]. The activation of GIT1 by integrin has been reported to be a signaling transduction mechanism.…”
Section: Discussionmentioning
confidence: 99%